Dark satisfaction in Guanajuato’s Mummies Museum visitors - Juan Gabriel Brida; Erika Lourdes González Rosas; María Nela Seijas Giménez (Journal of Tourism, Heritage & Services Marketing, 2023)
Purpose: The purpose of this study is to explain the determinants of the degree of visit satisfaction to the Guanajuato Mummies Museum. The study contributes to the literature related to perceptions and attitudes of museum visitors, by identifying what factors explain the satisfaction with the visit; as to the best of our knowledge, no similar investigation has been carried out yet.